Iron cycling in Arctic methane seeps - Wei-Li Hong; Pauline Latour; Simone Sauer; Arunima Sen; William P. Gilhooly; Aivo Lepland; Fotios Fouskas (Geo-Marine Letters, 2020)
Anoxic marine sediments contribute a significant amount of dissolved iron (Fe 2+ ) to the ocean which is crucial for the global carbon cycle. Here, we investigate iron cycling in four Arctic cold seeps where sediments are anoxic and sulfidic due to the high rates of methane-fueled sulfate reduction. We estimated Fe 2+ diffusive fluxes towards the oxic sediment layer to be in the range of 0.8 to 138.7 μmole/m 2 /day and Fe 2+ fluxes across the sediment-water interface to be in the range of 0.3 to 102.2 μmole/m 2 /day. Such variable fluxes cannot be explained by Fe 2+ production from organic matter–coupled dissimilatory reduction alone. We propose that the reduction of dissolved and complexed Fe 3+ as well as the rapid formation of iron sulfide minerals are the most important reactions regulating the fluxes of Fe 2+ in these cold seeps. By comparing seafloor visual observations with subsurface pore fluid composition, we demonstrate how the joint cycling of iron and sulfur determines the distribution of chemosynthesis-based biota.